Pendampingan Green School Melalui Pengolahan Sampah di SMK Bina Husada Indonesia - Munawaroh Munawaroh; Dewi Suri Damayanti; Dewi Susilawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Green school or adiwiyata is a school that supports global sustainability in everythingthat start with thingking aboaut the future, designing learning experiences for students that prepare them to lead the world towards a healthier, cleaner and more sustainable future (Kemdikbud, 2020). In other words, a green school is a school that is commited to developing programs to internalize environmental valuesinto all school activities. Garbage in the school environment must be controlled through rule of policies made by the school. These rules or policies must be implemented by all parties related to the school, starting from the principal, teachers, students, school official, student guardians and the community around the school. Assistance in establishing a green school will be carried out starting from 1. Brainstorming to the school about green schools, 2. Waste management workshops and training for teachers and students, 3. Green school assistance, 4. Results of activities. Brainstorming resulted in three agreements namely, teacher and student’ knowledge of green schools was still low, there was no waste management at schools and green schools had not yet been formed at SMK Bina Husada Mandiri. Waste processing workshops and training produce ecobricks made from plastic waste. Green school assitence produse three products namely ecobricksofas, a one day no plastic policy every Monday and Thursday and the green school organizational structure. The existing green school program can be maintained by the school as the person in charge of the school and still needs to develop other green school programs such as reforestation etc. Keywords : green school, adiwiyata